2014
DOI: 10.1590/s0100-06832014000600004
|View full text |Cite
|
Sign up to set email alerts
|

Composição diferencial das comunidades bacterianas na rizosfera de variedas de cana-de-açúcar

Abstract: RESUMOA cultura da cana-de-açúcar é de extrema importância no cenário agrícola nacional. No entanto, pouco se sabe sobre a estruturação das comunidades microbianas associadas aos solos e às rizosferas de tais plantas. O objetivo deste trabalho foi avaliar a estrutura e diversidade das comunidades de bactérias associadas ao solo e à rizosfera de seis variedades de cana-de-açúcar cultivadas no Estado de São Paulo (Brasil). As análises foram realizadas com base em métodos independentes de cultivo, em que a técnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
3
0
5
Order By: Relevance
“…The bacterial classes Gammaproteobacteria and Betaproteobacteria comprised 65% of bacterial isolates (Table 1). The bacteria from this class responded to chemotactic factors of root exudates and were thus abundant in rhizospheric soils (Costa et al, 2014). However, the profile of exudates dif- fered according to genotype, phenological status, plant nutrition, and seasonality (Murphy et al, 2016).…”
Section: Phylummentioning
confidence: 99%
“…The bacterial classes Gammaproteobacteria and Betaproteobacteria comprised 65% of bacterial isolates (Table 1). The bacteria from this class responded to chemotactic factors of root exudates and were thus abundant in rhizospheric soils (Costa et al, 2014). However, the profile of exudates dif- fered according to genotype, phenological status, plant nutrition, and seasonality (Murphy et al, 2016).…”
Section: Phylummentioning
confidence: 99%
“…In sugarcane, the studies have focused on varieties cultivated in Southeast region of the country and have found important bacterial groups that perform BNF (Rennie et al, 1982;Oliveira et al, 2002;Loiret et al, 2004;Perin et al, 2004;Reis et al, 2004;Luvizotto et al, 2010;Costa et al, 2014). Resende et al (2006) reported that biological N 2 fixation (BNF) performed by bacteria associated with sugarcane can be responsible for up to 60% of the total N accumulated in the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Em todos os sistemas foram inoculados 1l de suspensão bacteriana a absorbância de 0,2(OD 600nm ). Todas as curvas de multiplicação celular foram realizadas em quadruplicadas, com leituras em absorbância com comprimento de onda 600nm (ZHANG et al, 2014) Estes resultados deram suporte à caracterização de um grupo de 280 isolados por meio da técnica de BOX-PCR, como utilizado em outros estudos que buscam uma melhor caracterização de culturas bacterianas (HUNGRIA et al, 2008;WONG, 2009;MARQUES et al, 2008;SOARES JÚNIOR et al, 2013 (COSTA et al, 2014;DINI-ANDREOTE et al, 2010;MENDES et al, 2007).…”
Section: Efeito Dos Exsudatos Radiculares Sobre O Desenvolvimento Dasunclassified
“…Devido a isto, estudos relativos ao aprimoramento das condições de cultivo são de grande interesse, surgindo diversas fontes de estudos, dentre as quais está à busca por um melhor conhecimento sobre as comunidades microbianas associadas ao processo produtivo da cana-de-açúcar. Actinobacterias (COSTA et al, 2014;DINI-ANDREOTE et al, 2010;MENDES et al, 2007;PHILIPPOT et al, 2013;PISA et al, 2011).…”
Section: Introductionunclassified